Predicting local tumour progression after ablation for colorectal liver metastases: CT-based radiomics of the ablation zone. Issue 141 (August 2021) - Staal, F.C.R.; Taghavi, M.; van der Reijd, D.J.; Gomez, F.M.; Imani, F.; Klompenhouwer, E.G.; Meek, D.; Roberti, S.; de Boer, M.; Lambregts, D.M.J.; Beets-Tan, R.G.H.; Maas, M.
Abstract: Purpose: To assess whether CT-based radiomics of the ablation zone (AZ) can predict local tumour progression (LTP) after thermal ablation for colorectal liver metastases (CRLM). Materials and methods: Eighty-two patients with 127 CRLM were included. Radiomics features (with different filters) were extracted from the AZ and a 10 mm periablational rim (PAR)on portal-venous-phase CT up to 8 weeks after ablation. Multivariable stepwise Cox regression analyses were used to predict LTP based on clinical and radiomics features. Performance (concordance [c]-statistics) of the different models was compared and performance in an 'independent' dataset was approximated with bootstrapped leave-one-out-cross-validation (LOOCV). Results: Thirty-three lesions (26 %) developed LTP. Median follow-up was 21 months (range 6−115). The combined model, a combination of clinical and radiomics features, included chemotherapy (HR 0.50, p = 0.024), cT-stage (HR 10.13, p = 0.016), lesion size (HR 1.11, p = <0.001), AZ_Skewness (HR 1.58, p = 0.016), AZ_Uniformity (HR 0.45, p = 0.002), PAR_Mean (HR 0.52, p = 0.008), PAR_Skewness (HR 1.67, p = 0.019) and PAR_Uniformity (HR 3.35, p < 0.001) as relevant predictors for LTP. The predictive performance of the combined model (after LOOCV) yielded a c-statistic of 0.78 (95 %CI 0.65−0.87), compared to the clinical or radiomics models only (c-statistic 0.74 (95 %CI 0.58−0.84) and 0.65 (95 %CI 0.52−0.83), respectively). Conclusion: Combining radiomics features with clinical features yielded a better performing prediction of LTP than radiomics only. CT-based radiomics of the AZ and PAR may have potential to aid in the prediction of LTP during follow-up in patients with CRLM.